Find the equation that is equivalent to the quadratic equation shown. Explain why x²  6x  27 = 0 A.) x(x  3) = 27 B.) (x  6)² = 63 C.) (x  3)² = 36 D.) (x
Mathematics
Anonym
Question
Find the equation that is equivalent to the quadratic equation shown. Explain why
x²  6x  27 = 0
A.) x(x  3) = 27
B.) (x  6)² = 63
C.) (x  3)² = 36
D.) (x  3)² = 28
x²  6x  27 = 0
A.) x(x  3) = 27
B.) (x  6)² = 63
C.) (x  3)² = 36
D.) (x  3)² = 28
1 Answer

1. User Answers TaylorBayley
C  (x3)^2=36
If we expand (x3)^2=36:
(x3)(x3)=36
x^23x3x+9=36
x^26x+9=36
Then subtract 36
x^26x27=0